CONSIDERATIONS ON THE VALUATION AND ACCOUNTING OF INVESTMENT PROPERTY IN THE CURRENT ECONOMIC ENVIRONMENT - Mariana BANUTA; Mihaela GADOIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
In recent years, an increasingly greater importance has been given to investment properties, which tend to become a reality of the assets of many companies. It is not hard to guess why the specialised bodies, namely the accounting normalization or valuation ones, have reserved distinctive sections of standards/regulations meant to provide recommendations for a credible valuation and an adequate recognition. This article approaches investment properties from multiple perspectives, emphasizing the manner of valuating the value of investment properties and of their correct accounting, thus creating the premises for the increase in the quality of the information used in the decisional acts of the information users.